Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Falah Inovasi Teknologi Jakarta - Muhammad Risel Ghathfan; Muhamad Azis Firdaus; Jani Subakti; Widhi Ariyo Bimo (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Factors that influence employee efficiency in completing tasks can be caused by individual factors and organizational environmental factors. A good work environment and discipline make work easier for employees. In this research the author uses quantitative data that can be measured or calculated directly expressed in numbers or numerical form or formulas. data collection techniques using Likert Scale Questionnaires. Based on the research results, the work environment does not have a significant influence on employee performance at PT. Falah Innovation Technology. Based on the regression results, the calculated t value is 1,572 t table 2,011. Work Discipline has a significant influence on Employee Performance at PT. Falah Innovation Technology, based on the regression results, the calculated t value is 3,586 t table 2,011. There is a positive influence between the Work Environment and Work Discipline on Employee Performance together, because F count is 20.127 (greater than) F table 3.20, meaning that the higher the value of the two independent variables, the higher the Employee Performance at PT. Falah Innovation. Technology.